Recruitment to Chromatin of (GA)n-Associated Factors GAF and Psq in the Transgenic Model System Depends on the Presence of Architectural Protein Binding Sites. - Chetverina, D.A.; Gorbenko, F.V.; Lomaev, D.V.; Georgiev, P.G.; Erokhin, M.M. (Doklady. Biochemistry and Biophysics, 2022)
Polycomb group (PcG) repressors and Trithorax group (TrxG) activators of transcription are essential for the proper development and maintenance of gene expression profiles in multicellular organisms. In Drosophila, PcG/TrxG proteins interact with DNA elements called PRE (Polycomb response elements). We have previously shown that the repressive activity of inactive PRE in transgenes can be induced by architectural protein-binding sites. It was shown that the induction of repression is associated with the recruitment of PcG/TrxG proteins, including the DNA-binding factors Pho and Combgap. In the present study, we tested the association of the two other PRE DNA-binding factors, GAF and Psq, with bxdPRE in the presence and absence of sites for architectural proteins. As a result, it was shown that both factors can be efficiently recruited to the bxdPRE only in the presence of adjacent binding sites for architectural proteins Su(Hw), CTCF, or Pita.